Spatial analysis of factors acting upon housing prices in Istanbul - E.Umran Topcu (European Regional Science Association (ERSA), 2010)
Istanbul is a rapidly growing city. With its stragetic location between two continents and having served three empires as a capital city, Istanbul holds a highly rich culture and history and has a high potential for growth. As for today, Istanbul is the most important trade, culture and tourism center of Turkey. Following the rural-urban migration of mid 20th. century, housing prices increased rapidly. Lower income groups failed to catch up with this increase and squatter housing ensued. Hence, the city went through a process of growth without sufficient physical and social infrastructure. Lack of identity happened to be an important indication of the process. The historical neighborhoods also had their share of the negative impacts through this process. While the prices in the squatter housing areas were lower, modern housing areas proliferated with their newer images and much higher prices, accordingly. New subcenters, augmented with the building of new bridges, new circular roads and their accompanying transportation facilities, caused the prices go even higher. Due to these reasons, cost of housing presents a wide variety according to locale and housing characteristics. This paper aims to analyze the factors acting upon housing prices according to location and find out guidelines that may direct the investors for more efficient housing investments.
Keywords: 330; Istanbul; housing prices; factors; location; impact